2007
DOI: 10.1097/01.prs.0000287136.22709.77
|View full text |Cite
|
Sign up to set email alerts
|

Myectomy and Botulinum Toxin for Paralysis of the Marginal Mandibular Branch of the Facial Nerve: A Series of 76 Cases

Abstract: Using myectomy for paralysis of the marginal mandibular branch of the facial nerve can be an effective treatment for this significant deformity. Chemical myectomy with botulinum toxin injection is a safe and convenient mode of treatment; however, the disadvantage is that it needs repeated injections and costs more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 14 publications
0
27
0
1
Order By: Relevance
“…In such a case, botulinum toxin can also be applied on the healthy side to reduce the muscle movements in the overused mimic areas. On the healthy side, botulinum toxin is most often used to reduce the function of the depressor anguli oris muscle [28]. …”
Section: Adjuvant Measuresmentioning
confidence: 99%
“…In such a case, botulinum toxin can also be applied on the healthy side to reduce the muscle movements in the overused mimic areas. On the healthy side, botulinum toxin is most often used to reduce the function of the depressor anguli oris muscle [28]. …”
Section: Adjuvant Measuresmentioning
confidence: 99%
“…Thus, if permanent paralysis is needed, a myotomy of the depressor labii could be performed by an endo-oral approach under local anesthesia. 25 Botulinum toxin also can be used in other areas, such as the forehead or the eye, depending on the features of the patient. 26 The treatment of facial palsies remains a great challenge for the surgeon, but an overall improvement in the results can be achieved using facial animation techniques involving neuromuscular transplants.…”
Section: Discussionmentioning
confidence: 99%
“…116 Blinded patient-reported measures of overall QOL, social functioning, personal appearance, visual function, and synkinesis severity demonstrated significant postinjection improvements for those in the BT treatment arm (P<.05, all measures) but not for saline placebo group (P>.05, all measures). Evidence from case series has demonstrated that in patients with flaccid paralysis, BT injection to the contralateral lip depressors improves lower-lip symmetry, 117 that injection into the contralateral NLF region improves oral competence, 118 and that injection into the contralateral forehead improves brow symmetry (level IV). 119 In addition, injectable fillers, such as hyaluronic acid, hydroxyapatite, and fat grafts, may be beneficial in the midface and lips (level V).…”
Section: Injectablesmentioning
confidence: 98%